UNIVARIATE ANALYSIS OF THE RELATIONSHIP BETWEEN THE ULTIMATE STRENGTH OF WIRE ROD AND THE PARAMETERS OF THE TECHNOLOGY OF ITS PRODUCTION - A. A. Bobrovnik (Литьë и металлургия)
Research of interrelations between parameters of the technology of rolled wire production and limit of its durability is carried out.